2006
DOI: 10.1523/jneurosci.4394-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Signaling Pathways Mediating Synaptic Potentiation Triggered by Amyotrophic Lateral Sclerosis IgG in Motor Nerve Terminals

Abstract: Sporadic amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease that affects particularly motoneurons. Several pieces of evidence suggested the involvement of autoimmune mechanisms mediated by antibodies in ALS. However, the significance of those antibodies in the disease and the underlying mechanisms are unknown. Here we showed that IgG purified from a group of sporadic ALS patients, but not familial ALS patients, specifically interact with the presynaptic membrane of motoneurons through an antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 65 publications
(108 reference statements)
5
56
0
7
Order By: Relevance
“…This is significant because many of the prevailing hypotheses, including SOD1 accumulation and mitochondrial dysfunction, have been considered from the perspective of cell death activation (Bruijn et al, 1998;Liu et al, 2004). Although this study is the first to completely dissociate MN death from MN dysfunction in a model of MN disease, previous studies have demonstrated deficits in the distal MN that significantly precede or occur independently of cell death (Sagot et al, 1995;Fischer et al, 2004;Pagani et al, 2006;Pun et al, 2006). Such a dissociation between synaptic and cell body loss observed in Bax KO/SOD1 mutant MNs is also consistent with the results of trophic deprivation or injury studies (Deckwerth and Johnson, 1994;Mattson et al, 1998;Raff et al, 2002;Berliocchi et al, 2005).…”
Section: Discussionmentioning
confidence: 82%
“…This is significant because many of the prevailing hypotheses, including SOD1 accumulation and mitochondrial dysfunction, have been considered from the perspective of cell death activation (Bruijn et al, 1998;Liu et al, 2004). Although this study is the first to completely dissociate MN death from MN dysfunction in a model of MN disease, previous studies have demonstrated deficits in the distal MN that significantly precede or occur independently of cell death (Sagot et al, 1995;Fischer et al, 2004;Pagani et al, 2006;Pun et al, 2006). Such a dissociation between synaptic and cell body loss observed in Bax KO/SOD1 mutant MNs is also consistent with the results of trophic deprivation or injury studies (Deckwerth and Johnson, 1994;Mattson et al, 1998;Raff et al, 2002;Berliocchi et al, 2005).…”
Section: Discussionmentioning
confidence: 82%
“…Asynchronous release is typically regarded as a result of Ca 2+ accumulation, and N-type Ca 2+ channels in the presynaptic terminals have been implicated in regulating the extent of asynchronous versus synchronous release (Hefft and Jonas, 2005;Pagani et al, 2006;Zakharenko et al, 1999). Of relevance to the present study, P/Q-type Ca 2+ channels are the predominant VDCCs involved in mediating synaptic transmission at the mature mammalian NMJ.…”
Section: Mechanisms Of Increased Asynchronous Release In App −/− Nmjmentioning
confidence: 85%
“…Aberrant activation of N-or L-type calcium channels has been observed when P/Q type VDCC or the adhesion protein NCAM are disrupted (Pagani et al, 2006;Polo-Parada et al, 2001;Urbano et al, 2001;Urbano et al, 2003). Of note, the N-type Ca 2+ channel is located farther away from the Ca 2+ sensor as compared with the P/Qtype channel (Wu et al, 1999), which increase the probability of Ca 2+ being bound by a calcium buffer like EGTA-AM, and would contribute to a higher extent of asynchronous release and greater synaptic depression at the presynaptic terminals (Hefft and Jonas, 2005;Pagani et al, 2006;Zakharenko et al, 1999). We thus reasoned that a disturbed calcium channel regulation may lead to aberrant Ca 2+ entry and contribute to the markedly increased asynchronous release and EGTA-AM sensitivity in APP deficient animals.…”
Section: Aberrant Ca 2+ Channel Activities At App −/− Nmjsmentioning
confidence: 99%
“…Autoantibodies to voltage-gated Ca 2+ or K + channels have been described in ALS patients, which induce specific motoneuron alterations both in vitro and in vivo after passive transfer in mice [174][175][176][177][178]. Accordingly, C5a and other complement activation products released after activation of the classical complement pathway by antibodies are elevated in the CSF and spinal cord of ALS mice and patients and specific inhibition of C5a receptor ameliorates disease in SOD1 G93A mice [179,180].…”
Section: The Neurotoxic Function Of the Immune Response In Alsmentioning
confidence: 99%